Building Effective Leadership Framing to Improve Organizational Performance - Ulvia Fatkurin Fuad (Journal of Innovative Islamic Education Management, 2026)
Organizational performance is strongly influenced by leadership effectiveness; however, in practice, many organizations still experience low performance due to weak leadership framing of vision, policies, and change. Unclear or inconsistent leadership framing often leads to confusion, resistance, and low employee engagement. Therefore, this study aims to analyze the role of effective leadership framing in improving organizational performance based on a literature review. This study employs a qualitative method using a library research approach. Data were obtained through a review of books, scholarly journals, and academic publications relevant to leadership framing, leadership communication, and organizational performance. Data analysis was conducted using content analysis and qualitative descriptive analysis. The findings indicate that clear, consistent, and meaningful leadership framing is able to shape positive employee perceptions, increase trust, motivation, and work commitment. Leadership framing also contributes to the formation of a visionary and adaptive work culture that supports the achievement of organizational performance. The implications of this study emphasize the importance of leadership framing as a practical leadership strategy that needs to be developed consciously and systematically to enhance organizational performance and sustainability.